THE HISTORY OF KHILAFIAH IN INDONESIA - Wisliy, Wisliy (JURNAL AL-AQIDAH, 2019)
The appearing Khilafiah in Indonesian Islamic History because of the side opinion of Ulama – Moslem Theologian – in using a nash as be an evidence in distinction of the rule of figh usage. It’s always influenced by the time and the condition, for instance among modernists and traditionalists acknowledge al Qur’an and as Sunnah are interpretable; while it’s also insisted by the aspect of government’s  politics as a need such as it’s happening until today. This writing uses the method of library research by using historical and content analysis approach. Key word : Khilafiah, Theology, Decision, Politics.